Analytical hierarchy process for justification of JIT implementations in Indian manufacturing industries. (2014) - Singh, Gurinder; Ahuja, Inderpreet Singh
Research on JIT had always been a major problem in the study on business management. The quality of product always depends upon the infrastructural sufficiency of the enterprise, its abilities to manage their human resources, equipment and facilities. The quality requirements and competitive price all over the world had forced organisations to use various manufacturing methods such as total quality management (TQM), total productive maintenance (TPM) and just-in-time (JIT) manufacturing effectively so as to achieve higher performances in business. This pragmatic research gauges the JIT critical factors to determine the strategic success factors in uncertain environment using analytical hierarchy process (AHP). The study outcome criteria include success rate of JIT as a whole as well as success rate of each input attribute of JIT. The research outcomes are applicable to manufacturing organisations in India, suggesting them the adoption of flexibility of JIT as a major antagonistic advantage with a higher ambiguity and delivery with a lower uncertainty.